Peer Collaboration of Six-year olds when Undertaking a Design Task - Yliverronen, Virpi; Marjanen, Päivi; Seitamaa-Hakkarainen, Pirita (Design and Technology Education: An International Journal, 2018)
The purpose of this study was to explore six-year-old Finnish preschoolers’ collaboration during a designing session, where they received a task to collaboratively design and sketch forest animals’ nests. Peer interaction is a natural part of craft, design and technology education because the learning situation itself provides various possibilities for collaboration. Craft making is traditionally seen as an individual execution, where makers are producing their own craft products instead of collaboration and shared outcomes. During this intervention, an experience of a shared designing and making situation was provided for children. The article focuses particularly on children’s verbal and embodied interactions, as well as children’s social roles in their groups, depending on their ability to use language during the designing process. Children’s activities were examined within Vygotsky’s sociocultural framework for learning and classified using a micro-level analysis methodology for tracking children’s collaboration and meaning making in designing. The results showed that six-yearold pre-schoolers succeeded in working collaboratively and they managed to solve the designing task with their peers, but embodied expressions also played a notable role in designing. Four types of roles, which children had in their peer groups, were found.